Genome‐wide association study of anterior uveitis - Koskimäki, Fredrika; Ahokas, Oona; Consortium, FinnGen; Team, Estonian Biobank Research; Elnahas, Abdelrahman; Reigo, Anu; Reis, Kadri; Esko, Tõnu; Palta, Priit; Leinonen, Sanna; Kettunen, Johannes; Liinamaa, Johanna; et al. (Acta ophthalmologica (Oxford, England), 2025)
Aims/Purpose: The purpose of this study was to identify new genetic associations of anterior uveitis through genome‐wide association study (GWAS). Methods: We conducted a GWAS meta‐analysis combining data from the FinnGen, Estonian Biobank and UK Biobank with a total of 12 205 cases and 917 145 controls. A phenome‐wide association study was performed to investigate associations across phenotypes and traits. Genetic correlations of anterior uveitis were evaluated. Results: We detected six anterior uveitis associated genomic regions with genome‐wide significance (p < 5 × 10‐8). Three novel loci were identified: INAVA, NLRP3 and NOS2. Three previously reported associations at HLA region, ERAP1 and TNRC18 were detected. All of these loci had biologically relevant genes involved in immunity. We also replicated associations at two loci previously associated with acute anterior uveitis (IL23R and HDAC2‐AS2). Phenome‐wide association study indicated that lead SNPs at three of the anterior uveitis associated loci (ERAP1, INAVA and TNRC18) are associated with other immunity‐related phenotypes, including ankylosing spondylitis and inflammatory bowel disease. A moderate genetic correlation between anterior uveitis and inflammatory bowel disease was found in genetic correlation analysis (rg = 0.39, p = 8 × 10‐5). Conclusions: We identified six anterior uveitis associated loci including three novel loci with genome‐wide significance. Our findings deepen our understanding of the genetic basis of anterior uveitis and the genetic connections between anterior uveitis and immune related disorders, providing a foundation for further research and potential therapeutic interventions.